METHODS OF USING MODELING TECHNOLOGIES FOR STUDENTS OF THE SPECIALTY USE OF HYDROTECHNIC INSTALLATIONS AND PUMPING STATIONS (American Journal of Pedagogical and Educational Research, 2025)
The article presents the importance of modeling programs in teaching specialist subjects to students of the specialty “the use of hydraulic structures and pumping stations”. Also, in the conditions of an informed society, the development of Information Communication is based on the important stages of the development of the education of our country, the need to equip educational institutions with digital and modern educational technologies, as well as the need to learn how to develop techniques and at the same time use modeling programs.In addition, some of the best options for learning how to prepare modeling for students of the specialty” the use of hydraulic structures and pumping stations for both video games and professional projects " are mentioned, as well as a look at the activities of scientists who conducted research on these problems.